ATV - Ch. Baerlocher; W.M. Meier; D.H. Olson (Atlas of Zeolite Framework Types, 2001)
Lifestyle behaviors such as diet, physical activity, and sleep play a prominent role at every stage of cardiometabolic disease. These behaviors follow daily, circadian rhythms in humans. These endogenous biological rhythms are controlled by an autonomous molecular clock present in every cell of the body. This presents a translational mismatch wherein in-clinic human procedures are typically performed on awake, active individuals in a fed state, whereas in-laboratory procedures on rodents are often conducted in the daytime during their inactive, rest phase, when they are minimally motivated to eat. This American Heart Association scientific statement is intended to raise awareness that time of day is a biological variable that must be considered as a key modulatory factor in all facets of biomedical research from basic to clinical science. The entirety of the cardiovascular and renal systems function in a circadian fashion, making the time of day critically important in understanding basic and clinical research. This daily variability ranges from gene expression to functional outputs and everything in between. Here, we provide rationale for why time of day needs to be considered in various aspects of experimental design and interpretation in research and provide what we believe are useful suggestions to strengthen the rigor and utility of cardiometabolic and kidney research.